Highly corrosion-resistant rubber containing tetrafluoroethylene, preparation method and application thereof
By adding whisker-doped bentonite agent and hydroxyapatite agent to the rubber, combined with the twin-screw extruder treatment, the shortcomings of existing rubber in terms of wear resistance, mechanical properties and corrosion resistance are solved, and efficient and stable performance improvement is achieved.
Patent Information
- Application Number
- CN202411851201.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
The existing rubber containing tetrafluoroethylene is in containers and pipes of spray robots or drones. The product has poor wear resistance and mechanical properties, and has poor corrosion resistance and solvent resistance, which limits the product's use efficiency.
Polytetrafluoroethylene and 120 Mooney viscosity binary fluoroelastomer raw rubber were used as the matrix material, and whisker-doped bentonite agent and hydroxyapatite agent were added, and high corrosion resistance rubber was prepared by a twin-screw extruder.
It significantly improves the wear resistance and mechanical properties of rubber, while improving corrosion resistance and solvent resistance, and improving product usage efficiency.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber, and in particular to a highly corrosion-resistant rubber containing tetrafluoroethylene, a preparation method and application thereof. Background Art
[0002] Rubber molecules contain fluorine atoms. The CF composed of fluorine atoms and carbon atoms has high performance. At the same time, fluorine atoms have a great adsorption effect, which enhances the performance of the CC bond in the fluorocarbon molecular chain and increases with the increase of its fluorination degree. Fluorine atoms can better shield the CC main bond to ensure the chemical inertness of the CC bond. For the application of tetrafluoroethylene in containers and pipes of spray robots or drones, the product has poor wear resistance and mechanical properties, and rubber wear resistance and mechanics are difficult to coordinate. At the same time, the product has poor corrosion resistance and solvent resistance, which limits the product's use efficiency. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a highly corrosion-resistant rubber containing tetrafluoroethylene, a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for preparing a highly corrosion-resistant rubber containing tetrafluoroethylene, which is characterized by comprising the following steps: Step 1: Weigh the raw materials by weight: 25-30 parts of polytetrafluoroethylene, 30-35 parts of binary fluororubber raw rubber with a Mooney viscosity of 120, 2-5 parts of vulcanizing agent, 2-5 parts of stearic acid, 4-7 parts of bentonite agent doped with whiskers, 5-7 parts of hydroxyapatite agent, 1-3 parts of antioxidant, and 2-4 parts of bismaleimide; Step 2: The raw materials of step 1 are blended evenly, and then sent into a twin-screw extruder for extrusion at a temperature of 170-175° C. After the extrusion is completed, a highly corrosion-resistant rubber containing tetrafluoroethylene is obtained.
[0005] Preferably, the vulcanizing agent is sulfur; and the antioxidant is antioxidant 4010NA.
[0006] Preferably, the preparation method of the whisker-doped bentonite agent is: S1: The bentonite is first heat treated at 210-230°C for 5-10 minutes, then cooled to room temperature at a rate of 1-3°C / min, and then mixed with a sufficient amount of 5% by mass sodium lignin sulfonate solution to obtain a bentonite solution; S2: adding 2-4 parts of silicon carbide whiskers and 1-3 parts of nano-silica sol to 4-7 parts of lanthanum chloride solution, and then adding 2-3 parts of silane coupling agent, stirring well, to obtain whisker solution; S3: The bentonite solution and the whisker solution are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent doped with whiskers.
[0007] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%.
[0008] Preferably, the silane coupling agent is silane coupling agent KH560.
[0009] Preferably, the preparation method of the hydroxyapatite agent is: S11: irradiating the hydroxyapatite in a proton irradiation box, and obtaining an irradiated hydroxyapatite agent after the irradiation is completed; S12: 3-5 parts of irradiated hydroxyapatite agent, 2-4 parts of chitosan solution, 1-3 parts of citric acid, and 3-5 parts of flake graphene are mixed to obtain a treatment agent; S13: The irradiated hydroxyapatite agent and the treatment agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the hydroxyapatite agent.
[0010] Preferably, the irradiation power of the irradiation treatment is 350-400W, and the irradiation time is 5-10 minutes.
[0011] Preferably, the mass fraction of the chitosan solution is 2-5%.
[0012] The invention also provides a method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene to prepare the highly corrosion-resistant rubber.
[0013] A highly corrosion-resistant rubber containing tetrafluoroethylene is used in containers and pipes of spray robots or drones.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The high corrosion resistance rubber of the present invention adopts polytetrafluoroethylene and binary fluororubber raw rubber with a Mooney viscosity of 120 as the base material, and is coordinated by adding a bentonite agent doped with whiskers and a hydroxyapatite agent. The wear resistance and mechanical coordination of the rubber of the product are improved, and the corrosion resistance and solvent resistance of the product have remarkable stability. DETAILED DESCRIPTION
[0015] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene of the present embodiment is characterized by comprising the following steps: Step 1: Weigh the raw materials by weight: 25-30 parts of polytetrafluoroethylene, 30-35 parts of binary fluororubber raw rubber with a Mooney viscosity of 120, 2-5 parts of vulcanizing agent, 2-5 parts of stearic acid, 4-7 parts of bentonite agent doped with whiskers, 5-7 parts of hydroxyapatite agent, 1-3 parts of antioxidant, and 2-4 parts of bismaleimide; Step 2: The raw materials of step 1 are blended evenly, and then sent into a twin-screw extruder for extrusion at a temperature of 170-175° C. After the extrusion is completed, a highly corrosion-resistant rubber containing tetrafluoroethylene is obtained.
[0017] The vulcanizing agent in this embodiment is sulfur; the antioxidant is antioxidant 4010NA.
[0018] The preparation method of the whisker-doped bentonite agent of the present embodiment is as follows: S1: The bentonite is first heat treated at 210-230°C for 5-10 minutes, then cooled to room temperature at a rate of 1-3°C / min, and then mixed with a sufficient amount of 5% by mass sodium lignin sulfonate solution to obtain a bentonite solution; S2: adding 2-4 parts of silicon carbide whiskers and 1-3 parts of nano-silica sol to 4-7 parts of lanthanum chloride solution, and then adding 2-3 parts of silane coupling agent, stirring well, to obtain whisker solution; S3: The bentonite solution and the whisker solution are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent doped with whiskers.
[0019] The mass fraction of the lanthanum chloride solution of the present embodiment is 2-5%.
[0020] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0021] The preparation method of the hydroxyapatite agent of this embodiment is: S11: irradiating the hydroxyapatite in a proton irradiation box, and obtaining an irradiated hydroxyapatite agent after the irradiation is completed; S12: 3-5 parts of irradiated hydroxyapatite agent, 2-4 parts of chitosan solution, 1-3 parts of citric acid, and 3-5 parts of flake graphene are mixed to obtain a treatment agent; S13: The irradiated hydroxyapatite agent and the treatment agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the hydroxyapatite agent.
[0022] The irradiation power of the irradiation treatment in this embodiment is 350-400W, and the irradiation time is 5-10 minutes.
[0023] The mass fraction of the chitosan solution in this embodiment is 2-5%.
[0024] The highly corrosion-resistant rubber prepared by the method for preparing highly corrosion-resistant rubber containing tetrafluoroethylene in this embodiment.
[0025] Example 1. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene of the present embodiment is characterized by comprising the following steps: Step 1: Weigh the raw materials by weight: 25 parts of polytetrafluoroethylene, 30 parts of binary fluororubber raw rubber with a Mooney viscosity of 120, 2 parts of vulcanizing agent, 2 parts of stearic acid, 4 parts of bentonite agent doped with whiskers, 5 parts of hydroxyapatite agent, 1 part of antioxidant, and 2 parts of bismaleimide; Step 2: The raw materials of step 1 are blended evenly, and then sent into a twin-screw extruder for extrusion at a temperature of 170° C. After the extrusion is completed, a highly corrosion-resistant rubber containing tetrafluoroethylene is obtained.
[0026] The vulcanizing agent in this embodiment is sulfur; the antioxidant is antioxidant 4010NA.
[0027] The preparation method of the whisker-doped bentonite agent of the present embodiment is as follows: S1: The bentonite is first heat treated at 210°C for 5 minutes, then cooled to room temperature at a rate of 1°C / min, and then mixed with a sufficient amount of 5% by mass sodium lignin sulfonate solution to obtain a bentonite solution; S2: adding 2 parts of silicon carbide whiskers and 1 part of nano-silica sol to 4 parts of lanthanum chloride solution, and then adding 2 parts of silane coupling agent, stirring well, to obtain a whisker solution; S3: The bentonite solution and the whisker solution are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent doped with whiskers.
[0028] The mass fraction of the lanthanum chloride solution of the present embodiment is 2%.
[0029] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0030] The preparation method of the hydroxyapatite agent of this embodiment is: S11: irradiating the hydroxyapatite in a proton irradiation box, and obtaining an irradiated hydroxyapatite agent after the irradiation is completed; S12: 3 parts of irradiated hydroxyapatite agent, 2 parts of chitosan solution, 1 part of citric acid, and 3 parts of flake graphene are mixed to obtain a treatment agent; S13: The irradiated hydroxyapatite agent and the treatment agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the hydroxyapatite agent.
[0031] The irradiation power of the irradiation treatment in this embodiment is 350W, and the irradiation time is 5 minutes.
[0032] The mass fraction of the chitosan solution in this embodiment is 2%.
[0033] The highly corrosion-resistant rubber prepared by the method for preparing highly corrosion-resistant rubber containing tetrafluoroethylene in this embodiment.
[0034] Example 2. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene of the present embodiment is characterized by comprising the following steps: Step 1: Weigh the raw materials by weight: 30 parts of polytetrafluoroethylene, 35 parts of binary fluororubber raw rubber with a Mooney viscosity of 120, 5 parts of vulcanizing agent, 5 parts of stearic acid, 7 parts of bentonite agent doped with whiskers, 7 parts of hydroxyapatite agent, 3 parts of antioxidant, and 4 parts of bismaleimide; Step 2: The raw materials of step 1 are blended evenly, and then sent into a twin-screw extruder for extrusion at an extrusion temperature of 175° C. After the extrusion is completed, a highly corrosion-resistant rubber containing tetrafluoroethylene is obtained.
[0035] The vulcanizing agent in this embodiment is sulfur; the antioxidant is antioxidant 4010NA.
[0036] The preparation method of the whisker-doped bentonite agent of the present embodiment is as follows: S1: The bentonite is first heat treated at 230°C for 10 min, then cooled to room temperature at a rate of 3°C / min, and then mixed with a sufficient amount of 5% by mass sodium lignin sulfonate solution to obtain a bentonite solution; S2: adding 4 parts of silicon carbide whiskers and 3 parts of nano-silica sol into 7 parts of lanthanum chloride solution, and then adding 3 parts of silane coupling agent, stirring well, to obtain whisker solution; S3: The bentonite solution and the whisker solution are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent doped with whiskers.
[0037] The mass fraction of the lanthanum chloride solution of the present embodiment is 5%.
[0038] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0039] The preparation method of the hydroxyapatite agent of this embodiment is: S11: irradiating the hydroxyapatite in a proton irradiation box, and obtaining an irradiated hydroxyapatite agent after the irradiation is completed; S12: 5 parts of irradiated hydroxyapatite agent, 4 parts of chitosan solution, 3 parts of citric acid, and 5 parts of flake graphene are mixed to obtain a treatment agent; S13: The irradiated hydroxyapatite agent and the treatment agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the hydroxyapatite agent.
[0040] The irradiation power of the irradiation treatment in this embodiment is 400W, and the irradiation time is 10 minutes.
[0041] The mass fraction of the chitosan solution in this embodiment is 5%.
[0042] The highly corrosion-resistant rubber prepared by the method for preparing highly corrosion-resistant rubber containing tetrafluoroethylene in this embodiment.
[0043] Example 3. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene of the present embodiment is characterized by comprising the following steps: Step 1: Weigh the raw materials by weight: 27.5 parts of polytetrafluoroethylene, 32.5 parts of binary fluororubber raw rubber with a Mooney viscosity of 120, 3.5 parts of vulcanizing agent, 3.5 parts of stearic acid, 5.5 parts of bentonite agent doped with whiskers, 6 parts of hydroxyapatite agent, 2 parts of antioxidant, and 3 parts of bismaleimide; Step 2: The raw materials of step 1 are blended evenly, and then sent into a twin-screw extruder for extrusion at a temperature of 172° C. After the extrusion is completed, a highly corrosion-resistant rubber containing tetrafluoroethylene is obtained.
[0044] The vulcanizing agent in this embodiment is sulfur; the antioxidant is antioxidant 4010NA.
[0045] The preparation method of the whisker-doped bentonite agent of the present embodiment is as follows: S1: The bentonite is first heat treated at 220°C for 7.5 min, then cooled to room temperature at a rate of 2°C / min, and then mixed with a sufficient amount of 5% by mass sodium lignin sulfonate solution to obtain a bentonite solution; S2: Add 3 parts of silicon carbide whiskers and 2 parts of nano-silica sol to 5.5 parts of lanthanum chloride solution, then add 2.5 parts of silane coupling agent, stir well, and obtain whisker solution; S3: The bentonite solution and the whisker solution are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1250 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent doped with whiskers.
[0046] The mass fraction of the lanthanum chloride solution of the present embodiment is 3.5%.
[0047] The silane coupling agent of this embodiment is silane coupling agent KH560.
[0048] The preparation method of the hydroxyapatite agent of this embodiment is: S11: irradiating the hydroxyapatite in a proton irradiation box, and obtaining an irradiated hydroxyapatite agent after the irradiation is completed; S12: 4 parts of irradiated hydroxyapatite agent, 3 parts of chitosan solution, 2 parts of citric acid, and 4 parts of flake graphene are mixed to obtain a treatment agent; S13: The irradiated hydroxyapatite agent and the treatment agent are mixed in a weight ratio of 5:3, and the ball milling is performed at a ball milling speed of 1250 r / min for 2 h. After the ball milling is completed, the mixture is washed with water and dried to obtain the hydroxyapatite agent.
[0049] The irradiation power of the irradiation treatment in this embodiment is 370W, and the irradiation time is 7.5 minutes.
[0050] The mass fraction of the chitosan solution in this embodiment is 3.5%.
[0051] The highly corrosion-resistant rubber prepared by the method for preparing highly corrosion-resistant rubber containing tetrafluoroethylene in this embodiment.
[0052] Comparative Example 1. The difference from Example 3 is that no bentonite agent doped with whiskers is added.
[0053] Comparative Example 2. The difference from Example 3 is that no whisker liquid is added in the preparation of the whisker-doped bentonite agent.
[0054] Comparative Example 3. The difference from Example 3 is that no silicon carbide whiskers or nano-silica sol are added to the whisker liquid.
[0055] Comparative Example 4. The difference from Example 3 is that no hydroxyapatite agent is added.
[0056] Comparative Example 5. The difference from Example 3 is that the hydroxyapatite agent is not treated with a treating agent.
[0057] The products of Examples 1-3 and Comparative Examples 1-5 were tested under normal conditions, placed in 2% acid conditions for 24 hours, and placed in acetone solvent for 24 hours, and tested repeatedly 5 times. The performance tests are as follows:
[0058] It can be seen from Comparative Examples 1-5 and Examples 1-3 that the products of the present invention have excellent wear resistance and tensile mechanical properties, and are resistant to acid corrosion and solvent stability. The present invention does not add a bentonite agent doped with whiskers or a hydroxyapatite agent, and the performance of the product deteriorates significantly. In addition, the whisker liquid does not contain silicon carbide whiskers, nano-silica sol, or hydroxyapatite agent, and the performance of the product tends to deteriorate. Only by using the raw materials of the present invention, the product performance effect is most significant.
[0059] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0060] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a highly corrosion-resistant rubber containing tetrafluoroethylene, characterized in that: The following steps are involved: Step 1: Weigh the raw materials by weight: 25-30 parts of polytetrafluoroethylene, 30-35 parts of binary fluororubber raw rubber with a Mooney viscosity of 120, 2-5 parts of vulcanizing agent, 2-5 parts of stearic acid, 4-7 parts of bentonite agent doped with whiskers, 5-7 parts of hydroxyapatite agent, 1-3 parts of antioxidant, and 2-4 parts of bismaleimide; Step 2: The raw materials of step 1 are blended evenly, and then sent into a twin-screw extruder for extrusion at a temperature of 170-175° C. After the extrusion is completed, a highly corrosion-resistant rubber containing tetrafluoroethylene is obtained.
2. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene according to claim 1, characterized in that: The vulcanizing agent is sulfur; the antioxidant is antioxidant 4010NA.
3. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene according to claim 1, characterized in that: The preparation method of the whisker-doped bentonite agent is: S1: The bentonite is first heat treated at 210-230°C for 5-10 minutes, then cooled to room temperature at a rate of 1-3°C / min, and then mixed with a sufficient amount of 5% by mass sodium lignin sulfonate solution to obtain a bentonite solution; S2: adding 2-4 parts of silicon carbide whiskers and 1-3 parts of nano-silica sol to 4-7 parts of lanthanum chloride solution, and then adding 2-3 parts of silane coupling agent, stirring well, to obtain whisker solution; S3: The bentonite solution and the whisker solution are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent doped with whiskers.
4. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene according to claim 3, characterized in that: The mass fraction of lanthanum chloride solution is 2-5%.
5. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene according to claim 3, characterized in that: The silane coupling agent is silane coupling agent KH560.
6. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene according to claim 1, characterized in that: The preparation method of hydroxyapatite agent is as follows: S11: irradiating the hydroxyapatite in a proton irradiation box, and obtaining an irradiated hydroxyapatite agent after the irradiation is completed; S12: 3-5 parts of irradiated hydroxyapatite agent, 2-4 parts of chitosan solution, 1-3 parts of citric acid, and 3-5 parts of flake graphene are mixed to obtain a treatment agent; S13: The irradiated hydroxyapatite agent and the treatment agent are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 h. After the ball-milling is completed, the mixture is washed with water and dried to obtain the hydroxyapatite agent.
7. The method for preparing the highly corrosion-resistant rubber containing tetrafluoroethylene according to claim 6, characterized in that: The irradiation power of the irradiation treatment is 350-400W, and the irradiation time is 5-10min.
8. The method for preparing the highly corrosion resistant rubber containing tetrafluoroethylene according to claim 6, characterized in that: The mass fraction of the chitosan solution is 2-5%.
9. A highly corrosion-resistant rubber prepared by the method for preparing a highly corrosion-resistant rubber containing tetrafluoroethylene as claimed in any one of claims 1 to 8.
10. Use of the highly corrosion-resistant rubber containing tetrafluoroethylene as claimed in any one of claims 1 to 8 in containers and pipes of spray robots or drones.